Strategi Dinas Kependudukan Dan Catatan Sipil Kota Tanjungpinang Dalam Pemanfaatan Sistem Digital Melalui Aplikasi “Si Kancil” - Syaihidina Hefir; Zhahara Dwi Amanda (International Forum of Researchers and Lecturers, 2024)
Along with technological advances, the development of information in today's world has grown faster and faster, so that many agencies have improved the quality of their services in various ways. E-goverment is an information technology system developed by the government to improve public services by providing options for the public to get easy access to public information. The Tanjungpinang Population and Civil Registration Office (Disdukcapil) launched the Population and Civil Registration Information System (Sikancil) application. The creation of the Sikancil application is a demand from the Minister of Home Affairs (Mendagri) who wants to be able to streamline online services, as stated in Permendagri no. 7 of 2019 concerning online administrative services (Walo, 2021: 19). This study aims to determine how the Strategy of the Population and Civil Registry Office of Tanjungpinang City in utilizing the Digital System through the Sikancil Application at the Tanjungpinang Population and Civil Registration Office (Disdukcapil), the research method used is descriptive research method with a qualitative approach.